Subcritical CO2 shows no effect on liquid hot water pretreatment of poplar wood - Jimenez-Gutierrez, Jose M. (Chema); van der Wielen, Luuk A.M.; Straathof, Adrie J.J. (Bioresource Technology Reports, 2020)
peer-reviewed Pretreatment of lignocellulosic biomass is required for many biorefinery processes. Previous studies have described hydrolysis of hemicelluloses by using liquid hot water (LHW) pretreatment. We evaluated the effect of carbonic acid originating from pressurized carbon dioxide during LHW pretreatment of poplar. The conditions applied covered temperatures from 120 to 200 °C, pretreatment times from 5 to 240 min and pressures from 1.0 to 2.2 MPa CO2 or N2. The pressure and the type of gas (CO2 or N2) did not have an effect on production of acetic acid, which functioned as a marker of progress of biomass hydrolysis. Results suggested that the presence of carbonic acid in the process does not significantly contribute to acidification. Deacetylation of lignocellulosic biomass can be achieved by LHW pretreatment irrespective of pressure and of gas type used, at the conditions tested.